Ascending aortic extension to increase aortopulmonary space after comprehensive stage II palliation. (9th December 2021) - Brancaccio, Gianluca; Trezzi, Matteo; Secinaro, Aurelio; Iacobelli, Roberta; Perri, Gianluigi; Filippelli, Sergio; Bordonaro, Veronica; Galletti, Lorenzo
Abstract: Aortic reconstruction at the time of the comprehensive stage II (CSII) procedure can be complicated by compression within the aortopulmonary space resulting in airway or pulmonary artery narrowing. We describe our experience with 2 patients with hypoplastic left heart syndrome and pulmonary artery stenosis after the CSII procedure. Both patients underwent an aortic extension with a Hemashield interposition graft to open up the aortopulmonary space. The patients were discharged from the hospital. In all cases the aortopulmonary space was enlarged, and the pulmonary arteries and airway were free from compression. Aortic extension is an option to be considered in children with pulmonary artery compression who previously had a CSII procedure. Abstract : Aortic reconstruction after a Norwood operation is crucial for the long-term outcome of patients with hypoplastic left heart syndrome (HLHS).